An Inquiry into Child Health and its Determinants: Application of Ordered Probit Model - Raut, Nirmal Kumar; Sah Karmayogi, Subodh Kumar (Economic Journal of Nepal, 2018)
This study analyzes determinants of child health 0 to 5 years old and compares those with the determinants of adolescent health 10 to19 years old. The particular focus is to test whether there exists socio-economic inequality and regional disparity in health of children and adolescents. It utilizes third wave of Nepal Living Standard Survey (NLSS-III) and further exploit ordered probit model to analyze the determinants. The results show the absence of socio-economic inequality in child health while sits presence in adolescent health. It is argued that factors other than income or socio-economic status like medical care, child rearing and breastfeeding matter for child health. However, the study finds regional disparity more pronounced in the health of children than adolescents. This difference may be attributed to the low-level of child-centered health awareness, high cost of access to health service facilities, and limited health service facilities specializing on child health in some regions. In addition, the study finds that caste, age of the child, and parental health status as major determinants of child health while age of the adolescent, education, and their parental health status as major determinants of adolescent health. Further, disaggregation of parental health status reveals that mother’s health status matter more. Finally, some recommendations are made for improving child health.